Mapping the Literature on Digital Marketing, Brand Image, Perceived Value, and Purchase Intention: A Bibliometric and Systematic Review - Diana Dwi Kusumasari; Budi Eko Soetjipto; Madziatul Churiyah (Economics and Business Journal (ECBIS), 2026)
consumer behavior. In recent years, digital marketing particularly through social media platforms has become an essential strategy for firms to enhance consumer engagement and influence purchasing decisions. Despite the growing body of literature on this topic, the relationships among digital marketing, brand image, perceived value, and purchase intention remain fragmented across previous studies. Therefore, this study aims to provide a comprehensive overview of the research landscape and identify emerging trends in this field. This study employs a Systematic Literature Review (SLR) combined with bibliometric analysis to examine publications related to digital marketing, brand image, perceived value, and purchase intention. Data were collected from the Scopus database covering the period from 2021 to 2026. Bibliometric mapping and keyword co-occurrence analysis were conducted using VOSviewer to identify research clusters, thematic structures, and the evolution of research topics. The findings reveal a significant increase in publications on digital marketing and consumer behavior in recent years, indicating growing academic interest in this field. The bibliometric analysis shows that social media marketing acts as a central theme connecting several key concepts such as brand image, perceived value, and purchase intention. Furthermore, overlay visualization indicates that emerging research topics include perceived value, consumer engagement, customization, and brand awareness, reflecting a shift toward a more holistic understanding of consumer experience in digital environments. This study contributes to the literature by mapping the intellectual structure and research evolution in the digital marketing domain and highlighting potential research directions for future studies. The findings also provide insights for researchers and practitioners in developing more integrated marketing strategies that enhance brand perception and perceived value to influence consumer purchase intention.